Statistical Modeling of Variability in Sediment-Water Nutrient and Oxygen Fluxes - Serpetti, Natalia; Witte, Ursula F. M.; Heath, Michael R. (Frontiers in Earth Science, 2016)
Organic detritus entering, or produced, in the marine environment is re-mineralised to inorganic nutrient in the seafloor sediments. The flux of dissolved inorganic nutrient between the sediment and overlying water column is a key process in the marine ecosystem, which binds the biogeochemical sub-system to the living food web. These fluxes are potentially affected by a wide range of physical and biological factors and disentangling these is a significant challenge. Here we develop a set of General Additive Models (GAM) of nitrate, nitrite, ammonia, phosphate, silicate and oxygen fluxes, based on a year-long campaign of field measurements off the north-east coast of Scotland. We show that sediment grain size, turbidity due to sediment re-suspension, temperature, and biogenic matter content were the key factors affecting oxygen consumption, ammonia and silicate fluxes. However, phosphate fluxes were only related to suspended sediment concentrations, whilst nitrate fluxes showed no clear relationship to any of the expected drivers of change, probably due to the effects of denitrification. Our analyses show that the stoichiometry of nutrient regeneration in the ecosystem is not necessarily constant and may be affected by combinations of processes. We anticipate that our statistical modelling results will form the basis for testing the functionality of process-based mathematical models of whole-sediment biogeochemistry.